Empirical proof of the empirical line - Baugh, W. M.; Groeneveld, D. P. (International journal of remote sensing, 2008)
Calibrating remotely sensed data to reflectance maximizes their quantitative utility. Many approaches exist for calibrating to reflectance (ρ), one of which is the empirical line (EL) method. It offers high-quality results, often to within a few per cent, but is demanding in terms of field work and analysis. The method assumes there is a linear relationship between raw digital numbers (DNs) (or radiance) and reflectance spectra of ground targets. While the EL technique is widely accepted, we have not found an exhaustive demonstration that there is a truly linear relationship between radiance/DN and reflectance factors. In this paper we present an empirical demonstration of the EL method using a data set that consists of 5304 ground spectra paired with Landsat Thematic Mapper (TM) pixels.